2020
DOI: 10.1002/ctm2.16
|View full text |Cite
|
Sign up to set email alerts
|

Acute lung injury in patients with COVID‐19 infection

Abstract: During the 2020 Spring Festival in China, the outbreak of a novel coronavirus, named COVID‐19 by WHO, brought on a worldwide panic. According to the clinical data of infected patients, radiologic evidence of lung edema is common and deserves clinical attention. Lung edema is a manifestation of acute lung injury (ALI) and may progress to hypoxemia and potentially acute respiratory distress syndrome (ARDS). Patients diagnosed with ARDS have poorer prognosis and potentially higher mortality. Although no effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 30 publications
0
90
0
2
Order By: Relevance
“…A Belgium study CT study of 216 confirmed COVID-19 patients, which involved the scoring of lung damage found that there were no differences between age or time from onset of the disease, but that men had more extensive lung damage (9.2 ± 5 versus 7.0 ± 4.8, p = 0.001) with a trend toward more bilateral lung involvement (89.3% versus 78.8%, p = 0.06) [72]. Even for those who do not go on to develop ARDS or ALI, there can be residual pathology, including alveolar damage and fibrosis that will compromise lung function in the longer term [73,74,75].…”
Section: Longer Term Health Implications For Menmentioning
confidence: 97%
“…A Belgium study CT study of 216 confirmed COVID-19 patients, which involved the scoring of lung damage found that there were no differences between age or time from onset of the disease, but that men had more extensive lung damage (9.2 ± 5 versus 7.0 ± 4.8, p = 0.001) with a trend toward more bilateral lung involvement (89.3% versus 78.8%, p = 0.06) [72]. Even for those who do not go on to develop ARDS or ALI, there can be residual pathology, including alveolar damage and fibrosis that will compromise lung function in the longer term [73,74,75].…”
Section: Longer Term Health Implications For Menmentioning
confidence: 97%
“…In addition to excessive lung inflammation through a cytokine storm, severe COVID-19 is characterized by pulmonary edema, following disruption of the microvascular endothelium (18), and by coagulopathy, which in many patients is characterized by pulmonary thrombosis (19). To test whether the excessive macrophage activation by anti-Spike IgG may contribute to pulmonary edema and thrombosis, we applied in vitro models for endothelial barrier integrity (20) and in situ thrombosis (21) using primary human pulmonary artery endothelial cells (HPAEC), where thrombocytes can be added under flow conditions.…”
Section: Main Textmentioning
confidence: 99%
“…The abnormalities associated with COVID-19 according to a study by Yoon et al (2020). In a study by Li et al (2020a), pathological alterations caused by the disease include lung edema and acute lung injury (ALI) which eventually caused acute respiratory distress syndrome (ARDS). ALI came as a result of the activation of the epithelial and endothelial cells and the consequent overproduction of proinflammatory cytokines.…”
Section: Effects Of Covid-19 To Human Lungsmentioning
confidence: 99%
“…Further, CT imaging studies have shown that the lesions are more concentrated on the lower lobes as well as the dorsal part of the lungs (Çinkooğlu et al, 2020). According to the radiologic evidence presented in a study by Li et al (2020a), the presence of edema and acute lung injury are common in critical stages of patients with severe COVID-19. Acute lung inflammation and long-term damage to the alveolar walls are among the main adverse effects suffered by COVID-19 survivors (Hosseiny et al, 2020;Xu et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%